2018
DOI: 10.1128/mra.01124-18
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Achromobacter spanius Strain 6, a Soil Bacterium Isolated from a Hydrocarbon-Degrading Microcosm

Abstract: Achromobacter spanius strain 6 is a Gram-negative soil bacterium isolated from a hydrocarbon-degrading microcosm. The draft genome sequence of A. spanius strain 6 is 6.57 Mb with a G+C content of 64.7% and 5,855 protein coding genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Shigella and Achromobacter are common soil bacterial groups (Santamaría and Toranzos 2003;Adam et al 2014;Farhadkhani et al 2018;Egea et al 2017;Furlan and Stehling 2017;Gunasekera et al 2018;Thulasi et al 2018; Garrido-Sanz et al 2018;Fang et al 2018), and they could colonize in plant tissues through plant roots (Liu et al 2011). Pantoea, Bacillus, Burkholderia, Sphingomonas, Limnobacter, Methylobacterium and so on often separated or identified by high frequency from various plant seeds were also detected from this research (Mantica et al 2010;Zhang et al 2018), some species in these genera can also improve the plant growth and production (Liu et al 2012a(Liu et al , 2018.…”
Section: Discussionsupporting
confidence: 54%
“…Shigella and Achromobacter are common soil bacterial groups (Santamaría and Toranzos 2003;Adam et al 2014;Farhadkhani et al 2018;Egea et al 2017;Furlan and Stehling 2017;Gunasekera et al 2018;Thulasi et al 2018; Garrido-Sanz et al 2018;Fang et al 2018), and they could colonize in plant tissues through plant roots (Liu et al 2011). Pantoea, Bacillus, Burkholderia, Sphingomonas, Limnobacter, Methylobacterium and so on often separated or identified by high frequency from various plant seeds were also detected from this research (Mantica et al 2010;Zhang et al 2018), some species in these genera can also improve the plant growth and production (Liu et al 2012a(Liu et al , 2018.…”
Section: Discussionsupporting
confidence: 54%
“…Dave et al (2014) observed an enhanced biodegradation of total polycyclic aromatic hydrocarbons (TPAHs) when using A. xylosoxidans , isolated from crude oil polluted marine sites. Gunasekera et al (2018) isolated a Achromobacter spanius strain which was present in the hydrocarbon-degrading bacterial community in a desert soil sample obtained under a fuel bladder.…”
Section: Resultsmentioning
confidence: 99%